Pembelajaran Bahasa Indonesia bagi Penutur asing berbasis Sektor Profesi melalui Pendekatatan Pembelajaran Kontekstual - Nurul Qomariah (Balai Bahasa Sulawesi Utara, 2011)
This writing is focused on teaching materials of BIPA (Indonesia for Foreign Speakers), namely the implementation of BIPA teaching profession through the sector-based approach to contextual learning. Departing from the plurality held by foreigners as language users and the diversity of areas of interest to their respective to their respective professions. the teaching of BIPA needs to be reviewed in terms of diversity by creating a classification based on aspects of the teaching professions of BIPA. The majority of learners BIPA professional sectors, namely education, economy, trade, tourism, and politics. Learning through contextual approach allows learners who come from various sectors of the profession can be met Indonesian will need to smooth job. Teaching materials sector-based approach to the profession by integrating contextual learning opportunities closer to the real situation of learners based on their profession and teaching materials that deal directly with the ﬁeld work.